PpMYB52 negatively regulates peach bud break through the gibberellin pathway and through interactions with PpMIEL1 - Zhang, Yuzheng; Tan, Qiuping; Wang, Ning; Meng, Xiangguang; He, Huajie; Wen, Binbin; Xiao, Wei; Chen, Xiude; Li, Dongmei; Fu, Xiling; Li, Ling (Frontiers in Plant Science, 2022)
Bud dormancy, which enables damage from cold temperatures to be avoided during winter and early spring, is an important adaptive mechanism of deciduous fruit trees to cope with seasonal environmental changes and temperate climates. Understanding the regulatory mechanism of bud break in fruit trees is highly important for the artificial control of bud break and the prevention of spring frost damage. However, the molecular mechanism underlying the involvement of MYB TFs during the bud break of peach is still unclear. In this study, we isolated and identified the PpMYB52 (Prupe.5G240000.1) gene from peach; this gene is downregulated in the process of bud break, upregulated in response to ABA and downregulated in response to GA. Overexpression of PpMYB52 suppresses the germination of transgenic tomato seeds. In addition, Y2H, Bimolecular fluorescence complementation (BiFC) assays verified that PpMYB52 interacts with a RING-type E3 ubiquitin ligase, PpMIEL1, which is upregulated during bud break may positively regulate peach bud break by ubiquitination-mediated degradation of PpMYB52. Our findings are the first to characterize the molecular mechanisms underlying the involvement of MYB TFs in peach bud break, increasing awareness of dormancy-related molecules to avoid bud damage in perennial deciduous fruit trees.